Bentuk dan Makna Sastra Lisan Parno Kerinci di Desa Jujun - Sandria, Dalmi; Suryani, Irma; Afria, Rengki (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study aims to describe and analyze the form and meaning of Parno Kerinci oral literature in Jujun, Kerinci Regency. This research approach is qualitative with descriptive type. The data in this study are utterances in the form of parno words in the Pusako Kenduri Ceremony at Jujun, Kerinci Regency, especially the form and meaning. The supporting data are the results of interviews with informants related to customary parno. The source of the data from this study is the parno text which has been recorded by the Jujun State Customary Density Institute. Data collection analysis techniques in this study were observation, documentation, observation, interviews, and notes. Based on the results of the study, it can be concluded that the form of traditional kerinci parno has its own uniqueness, because it is conveyed using the respective regional/village languages and delivered in beautiful language and rhythm. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis bentuk dan makna sastra lisan parno Kerinci di Jujun Kabupaten Kerinci. Pendekatan penelitian ini yaitu kualitatif dengan jenis deskriptif. Data dalam penelitiaan ini adalah tuturan yang berupa kata-kata parno dalam Upacara Kenduri pusako di Jujun Kabupaten Kerinci khususnya bentuk dan makna. Data pendukungnya adalah hasil wawancara peneliti dengan informan terkait dengan parno adat. Adapun sumber data dari penelitian ini yaitu teks parno yang sudah dibukukan oleh Lembaga Kerapatan Adat Negeri Jujun. Teknik analisis pengumpulan data dalam penelitian ini adalah observasi, dokumentasi, simak, wawancara, dan catat. Berdasarkan hasil penelitian, dapat disimpulkan bahwa bentuk parno adat kerinci memiliki keunikan tersendiri, karena disampaikan dengan menggunakan bahasa daerah/desa masing-masing dan disampaikan dengan bahasa dan irama yang indah.